Kolaborasi Orangtua-Guru dalam Pembiasaan Shalat Dhuha untuk Penguatan Karakter Religius Siswa Kelas Dua Sekolah Dasar - Agung Syah Putra (Sekolah Tinggi Agama Islam Taruna Surabaya, 2026)
Religious character education plays a crucial role in shaping the personality, morality, and spirituality of students from an early age. One of its practical implementations in elementary schools is the Dhuha prayer habituation program, which serves as a medium for instilling discipline, responsibility, and spiritual awareness. This study aims to analyze the role of parent–teacher collaboration in implementing Dhuha prayer habituation to strengthen the religious character of second-grade elementary school students. The study used a descriptive approach involving 30 students, 6 teachers, and 30 parents as participants. Data were collected through prayer activity observations, participation questionnaires, and in-depth interviews, then analyzed using descriptive quantitative and thematic qualitative techniques. The findings reveal that effective collaboration between parents and teachers—reflected through intensive communication, spiritual guidance, and consistent habituation at home and school—positively influences students’ discipline, responsibility, and religious awareness. The study emphasizes that sustainable synergy between families and schools is a key factor in the success of religious character education in elementary education.